2014
DOI: 10.1080/15287394.2013.861376
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Absorption, Disposition, and Exposure Assessment of Homosalate, a UV Filtering Agent, in Rats

Abstract: Homosalate (HMS) is an ultraviolet (UV) filtering agent used in sunscreens and other cosmetics for skin protection purposes. Despite the widespread use of these products, absorption, disposition, and in vivo endocrine disrupting potential of HMS have not been characterized. Thus, the aim of this study was to examine the percutaneous absorption, disposition, and exposure assessment of HMS in rats. Initially, sunscreen preparations of petrolatum jelly, oily solution, lotion, and gel were prepared and evaluated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…With the NOAEL of >2g/kg bw, the uncertainty factor (UF) of 100, and {the modifying factor (MF) of 3, the RDA of BAP was calculated as >6.67 mg/kg bw/d (or >400 mg/60 kg adult/d)}. The determination process of NOAEL is critical for human risk assessment to promote public health (Bolt et al, 2012;Choi et al, 2010;Meng et al, 2012;Dahshan et al, 2013;Kim et al, 2014). These data suggest that BAP used in this study may be considered safe for use in food, pharmaceutical, and cosmetic applications.…”
Section: Discussionmentioning
confidence: 99%
“…With the NOAEL of >2g/kg bw, the uncertainty factor (UF) of 100, and {the modifying factor (MF) of 3, the RDA of BAP was calculated as >6.67 mg/kg bw/d (or >400 mg/60 kg adult/d)}. The determination process of NOAEL is critical for human risk assessment to promote public health (Bolt et al, 2012;Choi et al, 2010;Meng et al, 2012;Dahshan et al, 2013;Kim et al, 2014). These data suggest that BAP used in this study may be considered safe for use in food, pharmaceutical, and cosmetic applications.…”
Section: Discussionmentioning
confidence: 99%
“…HMS may be attributed to high affinity binding to the lipophilic components of the skin layers. HMS absorb into the systemic circulation from skin after topical application of the gel formulation in rats [8]. Schlumpf et al [10] also found residues of HMS in breast milk samples.…”
Section: Discussionmentioning
confidence: 99%
“…It is also reported that some skinabsorbed UV filters could result unknown systemic toxic effects [6]. However, recent studies have shown that organic UV filters in certain formulation -after absorption through the skin-have the potential of being metabolized and excreted [7,8]. Now that many organic UV filters are lipophilic, they can easily bioaccumulate and biomagnify in aquatic ecosytems, where their impact is a big concern.…”
Section: Introductionmentioning
confidence: 99%
“…Homosalate (HMS) is an UV filtering agent used in sunscreens and other cosmetics for skin protection purposes. It is a viscous or light yellow to slightly tan liquid or oil, derives from salicylic acid [70,71]. Salicylates are weak UVB absorbers and they are generally used in combination with other UV filters.…”
Section: Homosalatementioning
confidence: 99%